Microglial Acid Sensing Regulates Carbon Dioxide-Evoked Fear - Vollmer, Lauren Larke; Ghosal, Sriparna; McGuire, Jennifer L.; Ahlbrand, Rebecca L.; Li, Ke-Yong; Santin, Joseph M.; Ratliff-Rang, Christine A.; Patrone, Luis G. A. [UNESP]; Rush, Jennifer; Lewkowich, Ian P.; Herman, James P.; Putnam, Robert W.; et al. (Elsevier B.V., 2016)
BACKGROUND: Carbon dioxide (CO2) inhalation, a biological challenge and pathologic marker in panic disorder, evokes intense fear and panic attacks in susceptible individuals. The molecular identity and anatomic location of CO2-sensing systems that translate CO2-evoked fear remain unclear. We investigated contributions of microglial acid sensor T cell death-associated gene-8 (TDAG8) and microglial proinflammatory responses in CO2-evoked behavioral and physiological responses. METHODS: CO2-evoked freezing, autonomic, and respiratory responses were assessed in TDAG8-deficient ((-/-)) and wild-type (1/1) mice. Involvement of TDAG8-dependent microglial activation and proinflammatory cytokine interleukin (IL)-1 beta with CO2-evoked responses was investigated using microglial blocker, minocycline, and IL-1 beta antagonist IL-1RA. CO2-chemosensitive firing responses using single-cell patch clamping were measured in TDAG8(-/-) and TDAG8(+/+) mice to gain functional insights. RESULTS: TDAG8 expression was localized in microglia enriched within the sensory circumventricular organs. TDAG8(-/-) mice displayed attenuated CO2-evoked freezing and sympathetic responses. TDAG8 deficiency was associated with reduced microglial activation and proinflammatory cytokine IL-1 beta within the subfornical organ. Central infusion of microglial activation blocker minocycline and IL-1 beta antagonist IL-1RA attenuated CO2-evoked freezing. Finally, CO2-evoked neuronal firing in patch-clamped subfornical organ neurons was dependent on acid sensor TDAG8 and IL-1 beta. CONCLUSIONS: Our data identify TDAG8-dependent microglial acid sensing as a unique chemosensor for detecting and translating hypercapnia to fear-associated behavioral and physiological responses, providing a novel mechanism for homeostatic threat detection of relevance to psychiatric conditions such as panic disorder.
Keywords: Acid sensing; Carbon dioxide; Fear; Microglia; Panic; TDAG8